Negative outcomes associated with tyrosine kinase inhibitors during management of gastrointestinal stromal tumors: examination of data from the FDA adverse event reporting system - Ma, Yuxuan; Fan, Ahui; Wang, Yuhao; Xu, Shenhui; Liu, Xin; Yang, Jianjun (Frontiers in Oncology, 2025)
BackgroundSince the approval of Tyrosine kinase inhibitors (TKIs) in gastrointestinal stromal tumors (GISTs), the survival of patients with metastatic GISTs have been remarkably improved. But clinically, the adverse effects (AEs) are the major barrier to the long-term and standardized treatment and less reported.MethodsThe data was acquired from FDA Adverse Event Reporting System (FAERS) database from 2006 to 2024. TKIs were selected based on the clinical guidelines for the treatment of GISTs. AEs induced by different TKIs were analyzed using calculating reporting odds ratios (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma-Poisson shrinker (MGPS) to compare the character of safety signals of different TKIs.ResultsDisorders affecting skin and subcutaneous tissue, and the circulatory system emerged as the most common adverse events elicited by the majority of tyrosine kinase inhibitors. Meanwhile, some AEs only were observed in certain TKI. Endocrine disorders have higher risk only during the treatment with sunitinib, while avapritinib displayed unique AEs associated with nervous system disorders. Additionally, several significant signals were found on the preferred term (PT) level, including brain fog with avapritinib (ROR = 27.72), pemphigus (ROR = 30.90) with imatinib, nerve injury (ROR = 25.02) with ripretinib, tough blistering (ROR = 54.96) with sunitinib.ConclusionOur comprehensive pharmacovigilance analysis identified distinct adverse event profiles and significant drug-specific safety signals among TKIs used in GIST treatment. These findings enhance the characterization of TKI safety, revealing previously unreported or strongly associated signals and highlighting differences between agents. This evidence contributes to a better understanding of TKI-associated risks in clinical practice.